Pars plana vitrectomy with juxtapapillary laser photocoagulation versus vitrectomy without juxtapapillary laser photocoagulation for the treatment of optic disc pit maculopathy: the results of the KKESH International Collaborative Retina Study Group. Issue 4 (20th August 2015) - Abouammoh, Marwan A; Alsulaiman, Sulaiman M; Gupta, Vishali S; Mousa, Ahmed; Hirakata, Akito; Berrocal, Maria H; Chenworth, Megan; Chhablani, Jay; Oshima, Yusuke; AlZamil, Waseem M; Casella, Antonio Marcelo; Papa-Oliva, Gabriela; et al.
Abstract : Background/aims: To compare the functional and anatomic outcomes of pars plana vitrectomy (PPV) with juxtapapillary laser photocoagulation (JLP) versus vitrectomy without JLP in optic disc pit maculopathy. Methods: This was a multicentre, retrospective study of 46 consecutive patients with optic disc pit maculopathy presenting at tertiary eye centres between 1992 and 2012. Indications for surgery included distorted or decreased vision. Surgical intervention included PPV, posterior vitreous detachment, with or without gas tamponade. Twenty-four patients received laser photocoagulation at the temporal edge of the optic disc pit (group A) and 22 patients had no laser (group B). Postoperative best-corrected visual acuity (BCVA) and optical coherence tomography findings were the main outcome measures. Results: Mean follow-up was 44 months (range 12–98 months). BCVA in group A improved significantly from 0.7 logMAR (20/100) preoperatively to 0.5 logMAR (20/60) postoperatively (p=0.017). In group B, BCVA improved from 0.7 logMAR (20/100) preoperatively to 0.4 logMAR (20/40) postoperatively (p=0.014). The difference in final BCVA between groups was not statistically significant (p=0.693). The mean central macular thickness (CMT) in group A improved significantly from 750 μm preoperatively to 309 μm at last follow-up (p<0.0001). The mean CMT in group B improved from 616 μm preoperatively to 291 μm at last follow-up (p=0.028). The difference in final CMT between groups was not statistically significant (p=0.747). Conclusions: PPV with JLP for optic disc pit maculopathy had similar functional and anatomic outcomes compared with vitrectomy without JLP.